Literasi Penerapan Marketing Mix Pada Keripik Bayam Dalam Upaya Pembangunan Santripreneur di MAN Insan Cendekia Sorong - Andi Hasrun; Susetyowati Sofia; Rizka Cintya Edwar; Fadli Rabsani Raihan Yusuf; Ahmad Fajar; Ramlan Samu’a M; Awan Hyasmara; Agus Suyoto; Ayu Mandiran Yarkuran (Universitas 45 Surabaya, 2023)
Spinach is one of the raw materials that is easy to get in Southwest Papua, especially in Sorong, where it is widely sold in markets. The objectives of this activity are: 1). increase students' insight into marketing strategies, 2). increase students' insight into the application of the marketing mix applied to products, 3). provide motivation for students to become entrepreneurs, 4). The importance of marketing strategy in a business. Implementation of activities is carried out with the following steps: observation; completion of permits; training; discussion, reinforcement of material; and reporting. The marketing team provided material and socialization about marketing strategy literacy resulting from processed spinach business ideas to MAN Insan Scholar Sorong students. The activities carried out in this training are MAN IC students who take part in the training, especially class 11 students so that MAN Scholar students have the ability to implement product marketing well and have an entrepreneurial spirit without any fear of marketing.